A high-glue recycled composite SBS modified asphalt

Through the modification treatment of modified desulfurization powder and modified SBS and the introduction of modified nanofillers, the problem of segregation and precipitation of existing modified asphalt during storage and use is solved, and the performance and stability of the asphalt are significantly improved.

CN119192870BActive Publication Date: 2025-04-15JIANGSU ZENGGUANG COMPOSITE MATERIAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411468059.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-04-15
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

Existing modified asphalt is prone to segregation and precipitation during storage and use, which affects its working performance. In particular, the utilization of old tire rubber powder does not fully consider performance optimization and compatibility issues.

Method used

High-glue regeneration composite SBS modified asphalt is used to increase the number and compatibility of the reactive groups of the modified desulfurization glue powder and modified SBS through modification treatment, forming a stable polymer network structure, and introducing modified nanofillers to enhance the stability and performance of the asphalt.

Benefits of technology

It significantly improves the elasticity, fatigue resistance, high-temperature rutting resistance and low-temperature crack resistance of asphalt, enhances its durability in complex environments, and improves the strength, wear resistance and aging resistance of asphalt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005093944770000091
    Figure BDA0005093944770000091
  • Figure BDA0005093944770000101
    Figure BDA0005093944770000101
Patent Text Reader

Abstract

The present application relates to a high-rubber recycled composite SBS modified asphalt, and relates to the field of asphalt technology, which includes the following components by mass: 23-27 parts of modified desulfurized rubber powder, 4-5 parts of modified SBS, 0.5-1 parts of stabilizer, 2-3 parts of rubber oil, 58-62 parts of matrix asphalt, 2-3 parts of compatibilizer and 5-8 parts of modified nano filler. The present application has the effect of improving the compatibility between rubber powder, SBS and matrix asphalt, forming a polymer network structure with good stability, and effectively improving the low-temperature crack resistance, high-temperature rutting resistance and waterproof performance of the modified asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of asphalt, and in particular to a high-gel recycled composite SBS modified asphalt. Background Art

[0002] In the field of road engineering, with the continuous expansion of the expressway network and the increasing traffic volume, people's requirements for road materials are gradually increasing. In order to improve the durability and service life of roads, various types of modified asphalt are widely used in high-grade highway construction. These modified asphalts can significantly improve the rutting resistance, cracking resistance and waterproof performance of traditional asphalt pavement, thereby ensuring the long-term and stable use of roads.

[0003] In view of these needs, the prior art generally uses a variety of additives to improve the basic properties of the base asphalt in the process of producing modified asphalt, such as SBS (styrene-butadiene-styrene block copolymer) modifier, rubber powder and other auxiliary materials. SBS modifier is used to improve the mechanical properties of asphalt due to its good elasticity and toughness. Another commonly used additive is rubber powder, which can be a recycled product of waste tires. Adding it to asphalt can not only improve the fatigue resistance of the road, but also help environmental protection.

[0004] However, although the existing additives and modification schemes can improve the performance of asphalt to a certain extent, there are still significant deficiencies in practical applications, especially in the utilization of rubber powder from old tires. The traditional utilization method does not fully consider the performance optimization of rubber powder and the compatibility of rubber powder, SBS and base asphalt, which affects the stability of modified asphalt, making it easy to separate and precipitate during storage and use, thus affecting the working performance of asphalt, so it needs to be improved. Summary of the invention

[0005] In order to improve the stability of modified asphalt, the present application provides a high-gel recycled composite SBS modified asphalt.

[0006] The high-glue recycled composite SBS modified asphalt provided in this application adopts the following technical solution:

[0007] A high-glue recycled composite SBS modified asphalt, the raw materials for preparation include the following components in parts by weight:

[0008] Modified desulfurized rubber powder 23-27 parts

[0009] Modified SBS 4-5 parts

[0010] Stabilizer 0.5-1 part

[0011] 2-3 parts of rubber oil

[0012] Base asphalt 58-62 parts

[0013] 2-3 parts of extender

[0014] 5-8 parts of modified nano filler.

[0015] The modified desulfurized rubber powder and modified SBS are modified to increase the number of active groups and compatibility on their surfaces. Under the bridging and volume-increasing effect of the compatibilizer, a stable polymer network structure is formed, which can effectively improve the elasticity, fatigue resistance, high-temperature rutting resistance and low-temperature cracking resistance of asphalt, and enhance its durability in complex environments; the introduction of modified nanofillers greatly improves the strength, wear resistance and aging resistance of asphalt, reinforces the defects between the modified desulfurized rubber powder, modified SBS and matrix asphalt, increases physical cross-linking points, improves stability, and thereby improves the high-temperature rutting resistance and low-temperature cracking resistance of asphalt materials.

[0016] Preferably, the modified desulfurized rubber powder is prepared by the following steps:

[0017] The rubber powder is washed with water and then dried to obtain dried rubber powder, the dried rubber powder is subjected to microwave treatment to obtain desulfurized rubber powder, and the desulfurized rubber powder and a peroxide modifier are mixed and reacted to obtain modified desulfurized rubber powder.

[0018] Washing the rubber powder with water and drying it for dehydration can remove impurities and improve the purity of the rubber powder; the subsequent microwave treatment desulfurizes the rubber powder, changes its molecular structure, and enhances its compatibility and reactivity with asphalt; the desulfurized rubber powder is mixed with a peroxide modifier for reaction, and the peroxide modifier further destroys the cross-linking bonds inside the desulfurized rubber powder, improves its compatibility, and introduces new active groups on the molecular chain of the rubber powder, thereby improving the reactivity of the modified desulfurized rubber powder and enabling it to play a better role in high-rubber recycled composite SBS modified asphalt.

[0019] Preferably, the peroxide modifier comprises di-tert-butyl hydroperoxide.

[0020] The free radicals produced by the decomposition of di-tert-butyl hydroperoxide are highly active and can effectively further destroy the cross-linking structure of the rubber powder, thereby enhancing its compatibility with modified SBS and matrix asphalt; the reaction catalyzed by di-tert-butyl hydroperoxide requires a low reaction temperature, relatively low energy consumption, and the reaction is easy to control, which can reduce the performance degradation caused by excessive reaction and effectively improve the reaction performance and compatibility of the modified desulfurized rubber powder.

[0021] Preferably, the raw materials for preparing the modified SBS include SBS bulk, maleic anhydride and tetramethyltetravinylcyclotetrasiloxane.

[0022] The carboxylic acid group of maleic anhydride can react chemically with the double bonds in SBS, introducing polar functional groups on the SBS molecular chain, increasing the polarity of SBS, thereby improving the compatibility with modified desulfurized rubber powder and matrix asphalt, and promoting the uniform dispersion of modified SBS; tetramethyltetravinylcyclotetrasiloxane can improve the high-temperature stability of SBS and improve the high-temperature rutting resistance. Tetramethyltetravinylcyclotetrasiloxane has good hydrophobic properties and can improve the waterproof performance of modified SBS and reduce the damage of moisture to the asphalt structure. Tetramethyltetravinylcyclotetrasiloxane can also synergistically act with maleic anhydride to improve the bonding performance of modified SBS, improve the elasticity and flexibility of the road surface, and thus improve the low-temperature cracking resistance.

[0023] Preferably, the mass ratio of the SBS bulk, maleic anhydride and tetramethyltetravinylcyclotetrasiloxane is 1:0.03:(0.05-0.08).

[0024] The modified SBS prepared according to the above mass ratio has good compatibility and can effectively improve the low-temperature anti-cracking performance, high-temperature anti-rutting performance and waterproof performance of asphalt.

[0025] Preferably, the raw materials for preparing the compatibilizer include epoxy resin, hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide.

[0026] Hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide modified epoxy resin can introduce isocyanate groups and thioether groups into epoxy resin, increase the surface active groups of epoxy resin, improve the crosslinking degree of epoxy resin, and thus improve the stability of epoxy resin; the active groups on the compatibilizer can react with modified SBS and modified desulfurized rubber powder to enhance the binding force, compatibility and stability of the two, thereby improving the low-temperature crack resistance, high-temperature rutting resistance and waterproof performance of high-rubber recycled composite SBS modified asphalt.

[0027] Preferably, the mass ratio of the epoxy resin, hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide is 1:0.45:(0.1-0.18).

[0028] The compatibilizer prepared according to the above mass ratio has good reactivity and stability, and can effectively improve the low-temperature anti-cracking performance, high-temperature anti-rutting performance and waterproof performance of asphalt.

[0029] Preferably, the raw materials for preparing the modified nanofiller include composite nanofiller, silane coupling agent and decanediamine.

[0030] The silane coupling agent reacts with the hydroxyl groups on the composite nanofiller to increase the active groups on the surface of the nanofiller. Subsequently, it is further modified with decanediamine to give the composite nanofiller long amino chains that can react with the active double bonds and groups in the asphalt system, increase the cross-linking structure within the asphalt system, and improve the compatibility and stability of the system, thereby improving the low-temperature crack resistance, high-temperature rutting resistance and waterproof performance of the asphalt material.

[0031] Preferably, the composite nano-filler includes nano-silicon dioxide and nano-calcium carbonate.

[0032] Nano-silicon dioxide has a high specific surface area and high reactivity. Its surface hydroxyl groups can hydrogen bond and chemically bond with the active groups in modified desulfurized rubber powder and modified SBS, enhancing the interfacial bonding force between filler and polymer, thereby increasing the hardness, strength and toughness of asphalt materials, improving the high-temperature stability of asphalt materials, and reducing the occurrence of rutting and deformation; Nano-calcium carbonate can improve the rheological properties of asphalt, react with the acidic components in asphalt at high temperatures, reduce the viscosity of asphalt, and improve fluidity. At low temperatures, its nucleation effect can refine the crystallization of asphalt and enhance its low-temperature crack resistance. The filling effect of nano-calcium carbonate can increase the density of asphalt, enhance its water damage resistance and durability; Nano-silicon dioxide and nano-calcium carbonate work synergistically to effectively improve the low-temperature crack resistance, high-temperature rutting resistance and waterproof performance of asphalt materials.

[0033] Preferably, the high-gel recycled composite SBS modified asphalt is prepared by the following steps:

[0034] The modified desulfurized rubber powder and rubber oil are added to a twin-screw extruder for reaction after heating and stirring to obtain low Mooney rubber; modified SBS and a compatibilizer are added to the low Mooney rubber, heated for reaction, a stabilizer is added, the reaction is continued, and the material is discharged to obtain a composite modified material; the base asphalt is heated to a molten state, the prepared composite modified material and the modified nanofiller are mixed and dispersed in the molten base asphalt, heated and sheared, and discharged to obtain a high-rubber recycled composite SBS modified asphalt.

[0035] The high-rubber recycled composite SBS modified asphalt prepared according to the above steps has good low-temperature anti-cracking performance, high-temperature anti-rutting performance and waterproof performance.

[0036] In summary, the present application includes at least one of the following beneficial technical effects:

[0037] 1. The modified desulfurized rubber powder and modified SBS are modified to increase the number of active groups and compatibility on their surfaces. Under the bridging and volume-increasing effect of the compatibilizer, a stable polymer network structure is formed, which can effectively improve the elasticity, fatigue resistance, high-temperature rutting resistance and low-temperature cracking resistance of asphalt, and enhance its durability in complex environments; the introduction of modified nanofillers greatly improves the strength, wear resistance and aging resistance of asphalt, strengthens the defects between modified desulfurized rubber powder, modified SBS and matrix asphalt, increases physical cross-linking points, improves stability, and thus improves the high-temperature rutting resistance and low-temperature cracking resistance of asphalt materials.

[0038] 2. The carboxylic acid group of maleic anhydride can react chemically with the double bonds in SBS, introducing polar functional groups on the SBS molecular chain, increasing the polarity of SBS, thereby improving the compatibility with the modified desulfurized rubber powder and the matrix asphalt, and promoting the uniform dispersion of the modified SBS; tetramethyltetravinylcyclotetrasiloxane can improve the high-temperature stability of SBS and improve the high-temperature rutting resistance. Tetramethyltetravinylcyclotetrasiloxane has good hydrophobic properties and can improve the waterproof performance of the modified SBS and reduce the damage of moisture to the asphalt structure. Tetramethyltetravinylcyclotetrasiloxane can also synergize with maleic anhydride to improve the bonding performance of the modified SBS, improve the elasticity and flexibility of the road surface, and thus improve the low-temperature cracking resistance.

[0039] 3. Hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide modified epoxy resin can introduce isocyanate groups and thioether groups into epoxy resin, increase the surface active groups of epoxy resin, improve the crosslinking degree of epoxy resin, and thus improve the stability of epoxy resin; the active groups on the compatibilizer can react with modified SBS and modified desulfurized rubber powder to enhance the binding force, compatibility and stability of the two, thereby improving the low-temperature crack resistance, high-temperature rutting resistance and waterproof performance of high-rubber recycled composite SBS modified asphalt. DETAILED DESCRIPTION

[0040] The present application discloses a high-glue recycled composite SBS modified asphalt. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments:

[0041] Raw materials: di-tert-butyl hydroperoxide (CAS No.: 110-05-4), SBS (CAS No.: 9003-55-8), maleic anhydride (CAS No.: 108-31-6), tetramethyltetravinylcyclotetrasiloxane (CAS No.: 2554-06-5), azobisisobutyronitrile (CAS No.: 78-67-1), epoxy resin model E-51, hexamethylene diisocyanate (CAS No.: 822-06-0), propylene glycol methyl ether acetate ... S No.: 108-65-6), dibutyltin dilaurate (CAS No.: 77-58-7), bis(2-hydroxyethyl) disulfide (CAS No.: 1892-29-1), ethylene glycol methyl ether (CAS No.: 109-86-4), silane coupling agent is 4-biphenyldimethylchlorosilane (CAS No.: 41081-31-6), decanediamine (CAS No.: 646-25-3), rubber oil (CAS No.: 91995-70-9), and the stabilizer is zinc stearate.

[0042] Example 1

[0043] Preparation of modified desulfurized rubber powder

[0044] The rubber powder was washed three times with water to remove impurities, and then dehydrated in an oven at 60°C to obtain dried rubber powder. The dried rubber powder was treated under a microwave with a power of 800 W for 3 minutes to obtain desulfurized rubber powder. 50 kg of desulfurized rubber powder and 3 kg of di-tert-butyl hydroperoxide were mixed in a torque rheometer, mixed and reacted at a temperature of 180°C for 10 minutes and a rotation speed of 50 rpm to obtain modified desulfurized rubber powder.

[0045] Preparation of modified SBS

[0046] 9.26 kg of SBS, 0.28 kg of maleic anhydride and 0.46 kg of tetramethyltetravinylcyclotetrasiloxane were mixed and dispersed in a twin-screw extruder, 0.2 kg of azobisisobutyronitrile was added, and the mixture was reacted at 140° C. for 5 hours to obtain modified SBS.

[0047] Preparation of compatibilizer

[0048] 3.23 kg of epoxy resin and 1.45 kg of hexamethylene diisocyanate were mixed and dispersed in 10 L of propylene glycol methyl ether acetate to obtain a reaction solution, 10 g of dibutyltin dilaurate was added to the reaction solution, the temperature was raised to 60 ° C under nitrogen protection, and the reaction was carried out for 3 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain an intermediate product; 0.32 kg of bis (2-hydroxyethyl) disulfide and the intermediate product prepared above were dispersed in 10 L of ethylene glycol methyl ether, 5 g of dibutyltin dilaurate was added, the temperature was raised to 80 ° C and the reaction was carried out for 4 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain a compatibilizer.

[0049] Preparation of modified nanofillers

[0050] The composite nanofiller was mixed and ball-milled on a ball mill for 30 minutes, and the mass ratio of nano-silicon dioxide and nano-calcium carbonate in the composite nanofiller was 1:1, so as to obtain a composite nanofiller after ball milling; 10 kg of the composite nanofiller after ball milling and 2 kg of silane coupling agent were mixed and dispersed in 200 L of toluene, and stirred at a speed of 200 rpm for 2 hours, and then 0.5 L of deionized water was added, and the mixture was stirred and reacted at a speed of 200 rpm in a water bath at 80°C for 4 hours, and then 1.4 kg of decanediamine was added, and the mixture was stirred and reacted at a speed of 200 rpm in a water bath at 80°C for 4 hours, and the obtained product solution was filtered to obtain a filtrate, and the filtrate was washed with anhydrous ethanol, and the washed filtrate was dried in an oven at 80°C for 6 hours to obtain a modified nanofiller.

[0051] Preparation of high-resin recycled composite SBS modified asphalt

[0052] 23kg of modified desulfurized rubber powder and 2kg of rubber oil were stirred at 70°C at 200rpm for 30min, added into a twin-screw extruder and reacted at 200°C for 10min to obtain low Mooney rubber; 4kg of modified SBS and 2kg of bulking agent were added into the low Mooney rubber, reacted at 150°C for 20min, 0.5kg of stabilizer was added, reacted for 5min, and then discharged to obtain a composite modified material; 62kg of matrix asphalt was heated to a molten state, the prepared composite modified material and 5kg of modified nanofiller were mixed and dispersed into the molten matrix asphalt, sheared and developed at 180°C at 2000rpm for 3h, and discharged to obtain high-rubber recycled composite SBS modified asphalt.

[0053] Example 2

[0054] Preparation of modified desulfurized rubber powder

[0055] The rubber powder was washed three times with water to remove impurities, and then dehydrated in an oven at 60°C to obtain dried rubber powder. The dried rubber powder was treated under a microwave with a power of 800 W for 3 minutes to obtain desulfurized rubber powder. 50 kg of desulfurized rubber powder and 3 kg of di-tert-butyl hydroperoxide were mixed in a torque rheometer, mixed and reacted at a temperature of 180°C for 10 minutes and a rotation speed of 50 rpm to obtain modified desulfurized rubber powder.

[0056] Preparation of modified SBS

[0057] 9.01 kg of SBS, 0.27 kg of maleic anhydride and 0.72 kg of tetramethyltetravinylcyclotetrasiloxane were mixed and dispersed in a twin-screw extruder, 0.2 kg of azobisisobutyronitrile was added, and the mixture was reacted at 140° C. for 5 hours to obtain modified SBS.

[0058] Preparation of compatibilizer

[0059] 3.07 kg of epoxy resin and 1.38 kg of hexamethylene diisocyanate were mixed and dispersed in 10 L of propylene glycol methyl ether acetate to obtain a reaction solution, 10 g of dibutyltin dilaurate was added to the reaction solution, the temperature was raised to 60 ° C under nitrogen protection, and the reaction was carried out for 3 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain an intermediate product; 0.55 kg of bis (2-hydroxyethyl) disulfide and the intermediate product prepared above were dispersed in 10 L of ethylene glycol methyl ether, 5 g of dibutyltin dilaurate was added, the temperature was raised to 80 ° C and the reaction was carried out for 4 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain a compatibilizer.

[0060] Preparation of modified nanofillers

[0061] The composite nanofiller was mixed and ball-milled on a ball mill for 30 minutes, and the mass ratio of nano-silicon dioxide and nano-calcium carbonate in the composite nanofiller was 1:1, so as to obtain a composite nanofiller after ball milling; 10 kg of the composite nanofiller after ball milling and 2 kg of silane coupling agent were mixed and dispersed in 200 L of toluene, and stirred at a speed of 200 rpm for 2 hours, and then 0.5 L of deionized water was added, and the mixture was stirred and reacted at a speed of 200 rpm in a water bath at 80°C for 4 hours, and then 1.4 kg of decanediamine was added, and the mixture was stirred and reacted at a speed of 200 rpm in a water bath at 80°C for 4 hours, and the obtained product solution was filtered to obtain a filtrate, and the filtrate was washed with anhydrous ethanol, and the washed filtrate was dried in an oven at 80°C for 6 hours to obtain a modified nanofiller.

[0062] Preparation of high-resin recycled composite SBS modified asphalt

[0063] 27kg of modified desulfurized rubber powder and 3kg of rubber oil were stirred at 70°C at 200rpm for 30min, then added to a twin-screw extruder and reacted at 200°C for 10min to obtain low Mooney rubber; 5kg of modified SBS and 3kg of bulking agent were added to the low Mooney rubber, reacted at 150°C for 20min, 1kg of stabilizer was added, reacted for 5min, and then discharged to obtain a composite modified material; 58kg of matrix asphalt was heated to a molten state, the prepared composite modified material and 8kg of modified nanofiller were mixed and dispersed in the molten matrix asphalt, sheared and developed at 180°C at 2000rpm for 3h, and then discharged to obtain a high-rubber recycled composite SBS modified asphalt.

[0064] Example 3

[0065] Preparation of modified desulfurized rubber powder

[0066] The rubber powder was washed three times with water to remove impurities, and then dehydrated in an oven at 60°C to obtain dried rubber powder. The dried rubber powder was treated under a microwave with a power of 800 W for 3 minutes to obtain desulfurized rubber powder. 50 kg of desulfurized rubber powder and 3 kg of di-tert-butyl hydroperoxide were mixed in a torque rheometer, mixed and reacted at a temperature of 180°C for 10 minutes and a rotation speed of 50 rpm to obtain modified desulfurized rubber powder.

[0067] Preparation of modified SBS

[0068] 9.14 kg of SBS, 0.27 kg of maleic anhydride and 0.59 kg of tetramethyltetravinylcyclotetrasiloxane were mixed and dispersed in a twin-screw extruder, 0.2 kg of azobisisobutyronitrile was added, and the mixture was reacted at 140° C. for 5 hours to obtain modified SBS.

[0069] Preparation of compatibilizer

[0070] 3.14 kg of epoxy resin and 1.42 kg of hexamethylene diisocyanate were mixed and dispersed in 10 L of propylene glycol methyl ether acetate to obtain a reaction solution, 10 g of dibutyltin dilaurate was added to the reaction solution, the temperature was raised to 60 ° C under nitrogen protection, and the reaction was carried out for 3 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain an intermediate product; 0.44 kg of bis (2-hydroxyethyl) disulfide and the intermediate product prepared above were dispersed in 10 L of ethylene glycol methyl ether, 5 g of dibutyltin dilaurate was added, the temperature was raised to 80 ° C and the reaction was carried out for 4 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain a compatibilizer.

[0071] Preparation of modified nanofillers

[0072] The composite nanofiller was mixed and ball-milled on a ball mill for 30 minutes, and the mass ratio of nano-silicon dioxide and nano-calcium carbonate in the composite nanofiller was 1:1, so as to obtain a composite nanofiller after ball milling; 10 kg of the composite nanofiller after ball milling and 2 kg of silane coupling agent were mixed and dispersed in 200 L of toluene, and stirred at a speed of 200 rpm for 2 hours, and then 0.5 L of deionized water was added, and the mixture was stirred and reacted at a speed of 200 rpm in a water bath at 80°C for 4 hours, and then 1.4 kg of decanediamine was added, and the mixture was stirred and reacted at a speed of 200 rpm in a water bath at 80°C for 4 hours, and the obtained product solution was filtered to obtain a filtrate, and the filtrate was washed with anhydrous ethanol, and the washed filtrate was dried in an oven at 80°C for 6 hours to obtain a modified nanofiller.

[0073] Preparation of high-resin recycled composite SBS modified asphalt

[0074] 25kg of modified desulfurized rubber powder and 2.5kg of rubber oil were stirred at 70°C at 200rpm for 30min, then added to a twin-screw extruder and reacted at 200°C for 10min to obtain low Mooney rubber; 4.5kg of modified SBS and 2.5kg of bulking agent were added to the low Mooney rubber, reacted at 150°C for 20min, 0.75kg of stabilizer was added, reacted for 5min, and then discharged to obtain a composite modified material; 60kg of matrix asphalt was heated to a molten state, the prepared composite modified material and 6.5kg of modified nanofiller were mixed and dispersed in the molten matrix asphalt, sheared and developed at 180°C at 2000rpm for 3h, and discharged to obtain high-rubber recycled composite SBS modified asphalt.

[0075] Example 4

[0076] Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, di-tert-butyl hydroperoxide is replaced by diisopropylbenzene peroxide.

[0077] Example 5

[0078] Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of SBS bulk used is 9.44 kg, the amount of maleic anhydride used is 0.28 kg, and the amount of tetramethyltetravinylcyclotetrasiloxane used is 0.28 kg.

[0079] Example 6

[0080] Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the amount of SBS bulk used is 8.85 kg, the amount of maleic anhydride used is 0.27 kg, and the amount of tetramethyltetravinylcyclotetrasiloxane used is 0.88 kg.

[0081] Example 7

[0082] Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that maleic anhydride is not added when preparing the modified SBS in Example 7.

[0083] Example 8

[0084] Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of epoxy resin used is 3.33 kg, the amount of hexamethylene diisocyanate used is 1.5 kg, and the amount of bis(2-hydroxyethyl) disulfide used is 0.17 kg.

[0085] Example 9

[0086] Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the amount of epoxy resin used is 2.94 kg, the amount of hexamethylene diisocyanate used is 1.32 kg, and the amount of bis(2-hydroxyethyl) disulfide used is 0.74 kg.

[0087] Example 10

[0088] Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that hexamethylene diisocyanate is not added when preparing the compatibilizer in Example 10.

[0089] Embodiment 11

[0090] Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that no decanediamine is added when preparing the modified nanofiller in Example 11.

[0091] Example 12

[0092] Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, the composite nanofiller is replaced with nano-silicon dioxide when preparing the modified filler.

[0093] Comparative Example 1

[0094] Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the modified desulfurized rubber powder is replaced by desulfurized rubber powder.

[0095] Comparative Example 2

[0096] Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the modified SBS is replaced by SBS.

[0097] Comparative Example 3

[0098] Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, the compatibilizer is replaced by epoxy resin E-51.

[0099] Comparative Example 4

[0100] Comparative Example 4 is based on Example 3, and the only difference between Comparative Example 4 and Example 3 is that in Comparative Example 4, the modified nanofiller is replaced by nano-calcium carbonate.

[0101] Performance testing

[0102] (1) The "JTG F40-2004 Technical Specifications for Highway Asphalt Pavement Construction" was selected as the standard. Three specimens of each sample were prepared for anti-rutting performance testing. The dynamic stability of the specimens was tested at 60°C and a wheel pressure of 0.7 MPa. The average value was taken after measurement and the results are recorded in Table 1.

[0103] (2) Selecting "JTG F40-2004 Highway Asphalt Pavement Construction Technical Specifications" as the standard, prepare 250mm*30mm*35mm small beam specimens, and use three-point loading to increase the load at -10℃. Record the data when the specimen is damaged, calculate and record the low-temperature failure strain, prepare three specimens for each sample, take the average value after measurement, and record the results in Table 1.

[0104] (3) The "JTG E20-2011 Highway Engineering Asphalt and Asphalt Mixture Test Procedure" was selected as the standard. Three specimens were prepared for each sample. The immersion Marshall test and freeze-thaw splitting test were carried out. The immersion residual stability ratio and freeze-thaw splitting strength ratio were calculated and recorded. The average value was taken after measurement. The results are recorded in Table 1.

[0105] Table 1 Test results of high temperature anti-rutting performance, low temperature anti-cracking performance and waterproof performance of modified asphalt

[0106]

[0107]

[0108] It can be seen from Table 1 that the high-temperature dynamic stability of Examples 1-3 is greater than 11289 times, the low-temperature failure strain is greater than 3275, the water immersion residual stability ratio is greater than 89.5%, and the freeze-thaw splitting strength ratio is greater than 90.3%. It can be seen that the modified asphalt prepared in the present application has good high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance.

[0109] As can be seen from Table 1, the only difference between Example 4, Comparative Example 1 and Example 3 is that in Example 4, di-tert-butyl hydroperoxide is replaced by diisopropylbenzene peroxide, and in Comparative Example 1, the modified desulfurized rubber powder is replaced by desulfurized rubber powder. Compared with Example 3, the high-temperature anti-rutting performance, low-temperature anti-cracking performance and waterproof performance of Example 4 and Comparative Example 1 are reduced; this is because if di-tert-butyl hydroperoxide is replaced by diisopropylbenzene peroxide, a higher reaction temperature is required, and the cross-linking reaction is more intense, resulting in a decrease in the stability of the rubber powder and affecting the modification effect; and if no peroxide is added for further modification, the number of active groups is reduced, the compatibility of the desulfurized rubber powder is reduced, and thus the stability of the asphalt is reduced, and the high-temperature anti-rutting performance, low-temperature anti-cracking performance and waterproof performance are greatly reduced.

[0110] As shown in Table 1, the difference between Examples 5, 6, 7, and Comparative Example 2 and Example 3 is that the mass ratio of SBS body, maleic anhydride and tetramethyltetravinylcyclotetrasiloxane in Example 5 is 1:0.03:0.03, the mass ratio of SBS body, maleic anhydride and tetramethyltetravinylcyclotetrasiloxane in Example 6 is 1:0.03:0.1, maleic anhydride is not added when preparing modified SBS in Example 7, and the modified SBS is replaced by SBS in Comparative Example 2. Compared with Example 3, the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance of Examples 5, 6, 7 and Comparative Example 2 are greatly reduced; this is because if the SBS body, maleic anhydride and tetramethyltetravinylcyclotetrasiloxane are Tetravinylcyclotetrasiloxane is not within the specified range, and the components affect each other, which will reduce the modification effect and affect the stability and reaction performance of the modified SBS; if maleic anhydride is not added when preparing the modified SBS, the introduction of active groups is lacking, the reaction activity of the modified SBS decreases, and the compatibility with the modified desulfurized rubber powder and the matrix asphalt decreases, and the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance decrease to varying degrees; if the modified SBS is directly replaced by SBS, the introduction of active groups is lacking, and the gain effect of siloxane and maleic anhydride on SBS, the performance is further reduced, and the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance are greatly reduced.

[0111] As shown in Table 1, the difference between Examples 8, 9, 10 and Comparative Example 3 and Example 3 is that the mass ratio of epoxy resin, hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide in Example 8 is 1:0.45:0.05, the mass ratio of epoxy resin, hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide in Example 9 is 1:0.45:0.25, and hexamethylene diisocyanate is not added when preparing the compatibilizer in Example 10. The compatibilizer is replaced by epoxy resin E-51 in Comparative Example 3. Compared with Example 3, the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance of Examples 8, 9, 10 and Comparative Example 3 are greatly reduced; this is because the epoxy resin When the mass ratio of epoxy resin, hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide is not within the specified range, the reactivity of the compatibilizer decreases, and the bridging and compatibilizing effect on the modified desulfurized rubber powder and modified SBS decreases, thereby reducing the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance. If hexamethylene diisocyanate is not added, the number of active groups decreases, the reactivity decreases, and the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance all decrease. When the compatibilizer is directly replaced with the unmodified epoxy resin E-51, the number of active groups is further reduced, thereby further reducing the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance.

[0112] As can be seen from Table 1, the only difference between Examples 11, 12, Comparative Example 4 and Example 3 is that: in Example 11, no decanediamine is added when preparing the modified nanofiller, in Example 12, the composite nanofiller is replaced with nano-silicon dioxide when preparing the modified filler, and in Comparative Example 4, the modified nanofiller is replaced with nano-calcium carbonate. Compared with Example 3, Examples 11 and 12 have reduced high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance; this is because the components in the modified nanofiller are changed, the lack of decanediamine, the number of active groups is reduced, the reinforcing effect on the polymer network is reduced, the composition of the filler is reduced, and the synergistic effect between the fillers is reduced, thereby reducing the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance; replacing the modified nanofiller with nano-calcium carbonate lacks the synergistic effect of the compound and the volume-increasing modification treatment, the dispersibility is reduced and the number of active groups is reduced, thereby greatly reducing the high-temperature rutting resistance, low-temperature cracking resistance and waterproof performance.

[0113] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A high-rubber recycled composite SBS modified asphalt, characterized by: The raw materials for preparation include the following components in parts by weight: Modified desulfurized rubber powder 23-27 parts Modified SBS 4-5 parts Stabilizer 0.5-1 part 2-3 parts of rubber oil Base asphalt 58-62 parts 2-3 parts of extender 5-8 parts of modified nanofiller; The modified desulfurized rubber powder is prepared by the following steps: The rubber powder is washed with water and then dried to obtain dried rubber powder, the dried rubber powder is subjected to microwave treatment to obtain desulfurized rubber powder, and the desulfurized rubber powder is mixed with a peroxide modifier to obtain modified desulfurized rubber powder; The peroxide modifier includes di-tert-butyl hydroperoxide; The raw materials for preparing the modified SBS include SBS body, maleic anhydride and tetramethyltetravinylcyclotetrasiloxane; The mass ratio of the SBS bulk, maleic anhydride and tetramethyltetravinylcyclotetrasiloxane is 1:0.03:(0.05-0.08); The raw materials for preparing the compatibilizer include epoxy resin, hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide; The mass ratio of the epoxy resin, hexamethylene diisocyanate and bis(2-hydroxyethyl) disulfide is 1:0.45:(0.1-0.18); The raw materials for preparing the modified nanofiller include composite nanofiller, silane coupling agent and decanediamine; The composite nano filler comprises nano silicon dioxide and nano calcium carbonate.

2. The high-rubber recycled composite SBS modified asphalt according to claim 1, characterized in that: The high-rubber recycled composite SBS modified asphalt is prepared by the following steps: The modified desulfurized rubber powder and rubber oil are added to a twin-screw extruder for reaction after heating and stirring to obtain low Mooney rubber; modified SBS and a compatibilizer are added to the low Mooney rubber, heated for reaction, a stabilizer is added, the reaction is continued, and the material is discharged to obtain a composite modified material; the base asphalt is heated to a molten state, the prepared composite modified material and the modified nanofiller are mixed and dispersed in the molten base asphalt, heated and sheared, and discharged to obtain a high-rubber recycled composite SBS modified asphalt.

Citation Information

Patent Citations

  • Composite modified desulfurized rubber asphalt and preparation method thereof

    CN108727843A